Workshop on Deep Learning Transformation of Project Based Learning and Digitalization of KKG Cluster 1 North Sinjai - Charmila Tandi Rerung; Arga Arga; Siti Nurhalizah Mutia Aulria; Muhammad Arkanul Arba; Martono Martono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
This community service activity departs from the fact that most of the teachers who are members of the Teacher Working Group (KKG) Cluster 1 North Sinjai District is still carrying out learning in the old way, sit-note-memorize, without much room for students to think or create. On the other hand, the demands of the applicable curriculum actually encourage teachers to be able to design meaningful and project-based learning, as well as be fluent in using digital devices in the classroom. This gap between demands and reality is the background for the implementation of this workshop. The activity is designed in stages ranging from socialization of deep learning concepts, Project Based Learning (PjBL) design training, introduction to digital platforms, assistance in developing teaching tools, to project-based teaching simulations in groups. All teachers who are members of KKG Cluster 1 North Sinjai are actively involved, not just as listeners. Evaluation was carried out through direct observation, reflective discussions, and participant response questionnaires. The results are quite encouraging, teachers are beginning to understand what deep learning is and how to apply it through projects, are able to develop applicable learning project designs, and have dared to try several digital platforms to support the teaching process. More than that, their enthusiasm and confidence to innovate also grew. In the future, the PjBL approach combined with digitalization is expected not to stop at the training room, but to be truly implemented and developed sustainably in their respective schools.